Brassinosteroid homeostasis is critical for the functionality of the Medicago truncatula pulvinus. Issue 4 (26th January 2021) - Kong, Yiming; Meng, Zhe; Wang, Hongfeng; Wang, Yan; Zhang, Yuxue; Hong, Limei; Liu, Rui; Wang, Min; Zhang, Jing; Han, Lu; Bai, Mingyi; Yu, Xiaolin; et al.
Abstract: Many plant species open their leaves during the daytime and close them at night as if sleeping. This leaf movement is known as nyctinasty, a unique and intriguing phenomenon that been of great interest to scientists for centuries. Nyctinastic leaf movement occurs widely in leguminous plants, and is generated by a specialized motor organ, the pulvinus. Although a key determinant of pulvinus development, PETIOLULE-LIKE PULVINUS ( PLP ), has been identified, the molecular genetic basis for pulvinus function is largely unknown. Here, through an analysis of knockout mutants in barrelclover ( Medicago truncatula ), we showed that neither altering brassinosteroid (BR) content nor blocking BR signal perception affected pulvinus determination. However, BR homeostasis did influence nyctinastic leaf movement. BR activity in the pulvinus is regulated by a BR-inactivating gene PHYB ACTIVATION TAGGED SUPPRESSOR1 ( BAS1 ), which is directly activated by PLP . A comparative analysis between M. truncatula and the non-pulvinus forming species Arabidopsis and tomato ( Solanum lycopersicum ) revealed that PLP may act as a factor that associates with unknown regulators in pulvinus determination in M. truncatula . Apart from exposing the involvement of BR in the functionality of the pulvinus, these results have provided insights into whether gene functions among species are general or specialized. Abstract : Nyctinasty is triggered by the pulvinus, a motor organ located at the base of the leaf and brassinosteroids is involved in functionality of pulvinus for leaf movement.